(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tourism sector helps to understand the international facts and also supports the local cultural activities as well as handicraft items. in this context, the present paper is an attempt to explore the factors which affect the tourist satisfaction in hill areas. The study has been done with special reference to Valparai hill station. The place is located in the district of Coimbatore. The respondents are the tourists of tamilnadu who visited Valparai. The technique of sampling used to select the respondents is conveniounce sampling and the sample size of the study is 100. The tourists are asked to fill in a questionnaire for getting the required data of the study and the method used for analysis of data is Regression Analysis. The findings of the analysis show that there is significant relationship exists between factors and tourist satisfaction.